A technology review of electrodes and reaction mechanisms in vanadium redox flow batteries. Issue 33 (7th September 2015) - Kim, Ki Jae; Park, Min-Sik; Kim, Young-Jun; Kim, Jung Ho; Dou, Shi Xue; Skyllas-Kazacos, M.
<x xml:space="preserve">Abstract</x> The vanadium redox flow battery, which was first suggested by Skyllas-Kazacos and co-workers in 1985, is an electrochemical storage system which allows energy to be stored in two solutions containing different redox couples.